Agressão física e classe social Physical aggression and social class - Reinaldo J. Gianini; Julio Litvoc; José Eluf Neto (Universidade de São Paulo, 1999)
OBJETIVO: Considerando-se o aumento da violência e a escassez de informações sobre a relação classe social e vitimização por agressão física, realizou-se estudo com o objetivo de investigar esta associação. MÉTODOS: Foi adotado o estudo de caso-controle. Foram incluídos 191 casos de agressão física e 222 controles selecionados entre os indivíduos com queixas clínico-cirúrgicas não violentas, pareados por freqüência aos casos segundo sexo e idade, todos recrutados no período de 1/10/93 a 19/1/95, em pronto-socorro de Sorocaba, SP, Brasil. Foi aplicado questionário para obtenção de informações sobre classe social, cor, situação conjugal, hábito de fumar, ingestão de álcool e uso de drogas ilícitas. RESULTADOS: Ajustando-se os resultados por sexo, idade e os outros fatores estudados encontrou-se um risco de vitimização por agressão física significantemente maior para o subproletariado, com "Odds ratio" igual a 3,28 e Intervalo de Confiança de 95% igual a 1,42-7,59. CONCLUSÃO: Classe social é um fator importante no fenômeno da vitimização por agressão física, devendo o subproletariado receber atenção especial nas estratégias de intervenção para o problema. OBJECTIVE: Considering the increase of violence and the scarcity of informations about the relation between social class and victimization by physical aggression, a study was conducted to investigate this association. METHODS: A hospital-based case-control study. Cases and controls were recruited at a hospital, first-aid clinic, from 1/10/93 to 19/1/95. The study included 191 cases and 222 controls selected from among patients with non-violent clinical-surgical complaints, frequency-matched to cases by sex and age. Using a standardized questionnaire applied by trained interviewers, information obtained included social class, skin color, marital status, smoking habits, alcohol consumption and illicit drug use. RESULTS: Adjusting for sex and age, the risk of victimization by physical aggression was significantly higher for the subproletariat, Odds Ratio (OR) 4.20, 95% Confidence Interval (95% CI) 1.99-8.84; single (OR=2.10) or informal union (OR=2.62) as marital status (reference group = married); smokers of more than 10 cigarettes/day (OR=2.75); alcohol consumption (OR=2.08 for <=240 grams/week and OR=24.05 for >240 grams/week); and illicit drug users (OR=3.07). After adjusting for all factors studied a significant risk remained for the subproletariat (OR=3.28, 95% CI 1.42-7.59); single as marital status (OR=2.05, 95% CI 1.09-3.88); and alcohol consumption (OR=2.01, 95% IC 1.07-3.77 for <= 240 and OR=15.93, 95% CI 5.09-49.8 for >240 grams/week). CONCLUSION: Social class is an important factor in the phenomenon of victimization by physical aggression, with the subproletariat deserving special attention in the strategies of intervention regarding this problem.